Analisis Kinerja Coal Mill Unit 4 PT. PLN Indonesia Power UBP Pangkalan Susu - Moch Fikar Surahman (Jurnal Pengabdian Cendekia, 2026)
Coal Mill serves as a critical component in Steam Power Plants (PLTU) for pulverizing coal into fine powder ensuring efficient boiler combustion. This study aims to analyze the performance of Coal Mill Unit 4 at PT. PLN Indonesia Power UBP Pangkalan Susu, type MPS160HP-II. Quantitative descriptive research was conducted through field observation in June 2024. Population comprised 5 Coal Mill units (4 active, 1 standby), with sampling focused on one unit comparing design vs. actual data. Instruments included observation sheets and Central Control Room (CCR) data, analyzed using energy efficiency formula   and production efficiency  . Results revealed production efficiency of 89.5% and energy efficiency of 84.5%, below design standards due to 35% coal moisture, HGI 50, air-coal ratio 2.44, and mechanical wear. Conclusions recommend real-time coal quality monitoring, predictive maintenance, and air ratio optimization to achieve efficiency above 90%.